We are water protectors - Lindstrom, Carole, 1964- (Roaring Brook Press, a division of Holtzbrinck Publishing, 2020)
When a black snake threatens to destroy the Earth and poison her people's water, one young water protector takes a stand to defend Earth's most sacred resource. -- Publisher.